PENGGUNAAN PENDEKATAN SAINS TEKNOLOGI MASYARAKAT (STM) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS DI SDN KOTA BUKITTINGGI - Rahmiwati, Rahmiwati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
IPS Learning is subject aims to make the student can think critically, rationally, and creatively in response to emerging issues in their daily lives. But in previous learning makes learners difficulties in memorizing concepts that IPS Learners can not achieve the expected pembelajarn IPS. The purpose of this study was to describe the planning, execution, and learning outcomes using STM approach. This research is a classroom action research using qualitative and quantitative approaches. The results obtained with the use of the STM approach the average yield of the learning plan in the first cycle was 77 rose to 100 on sikus II, from the implementation aspects of the teacher’s 82 to 100, aspects of learners 83 to 98, then the average of the results of learners in the first cycle is 75 increased in the second cycle to 93 on sikus II. From the results of these studies shows that the study of students increased in all observable aspects.Kata Kunci; IPS; Pendekatan STM; Hasil Belajar